2014
DOI: 10.1016/j.cub.2014.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Far East Asian origin of lager beer yeast

Abstract: Lager-brewing arose in 15th century Bavaria [1] and is nowadays the most popular technique for alcoholic beverage production in the world. The technique is characterized by low temperature fermentation using the domesticated yeast Saccharomyces pastorianus (synonym S. carlsbergensis). It has been clear that the lager yeast is a hybrid with one portion of its genome having originated from S. cerevisiae ale yeast [2]. However, the source of the non-ale subgenome, which endows lager yeast with cold tolerance, had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
227
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(239 citation statements)
references
References 8 publications
9
227
0
3
Order By: Relevance
“…These results suggest that they are hybrid strains of S. cerevisiae and S. eubayanus. The hybrid origin of bottom brewing and wine yeast is often described in the literature (Bing et al, 2014, Libkind et al;Sipiczski, 2008 (Bing et al, 2014;Libkind et al, 2011;Sipiczski, 2008). U typového kmene S. pastorianus a S. pastorianus NCYC 396 došlo k amplifikaci pouze fragmentu o velikosti 228 bp, který je charakteristický pro S. eubayanus.…”
Section: ■ ■ 3 Results and Discussionmentioning
confidence: 99%
“…These results suggest that they are hybrid strains of S. cerevisiae and S. eubayanus. The hybrid origin of bottom brewing and wine yeast is often described in the literature (Bing et al, 2014, Libkind et al;Sipiczski, 2008 (Bing et al, 2014;Libkind et al, 2011;Sipiczski, 2008). U typového kmene S. pastorianus a S. pastorianus NCYC 396 došlo k amplifikaci pouze fragmentu o velikosti 228 bp, který je charakteristický pro S. eubayanus.…”
Section: ■ ■ 3 Results and Discussionmentioning
confidence: 99%
“…The fermentation temperature was determined based on our previous experiments and the temperature for the lager yeast was 2°C lower than the ale yeast. This cold tolerance of lager yeast is endowed by the non-ale subgenome (26). The growth curve showed that the yeast cell number varied over a wide range among different strains, which may be attributed to cell viability and flocculation properties.…”
Section: Discussionmentioning
confidence: 99%
“…Strong evidence has shown that lager yeast is a natural hybrid of two yeasts: S. cerevisiae and S. bayanus (27,28) or S. eubayanus (26,29). Hence, two relatively independent types of chromosome co-exist, with some rearrangement, in lager yeast: one set originating from S. cerevisiae (Sc-type) and another set from S. bayanus or S. eubayanus (Sb-or Se-type).…”
Section: Discussionmentioning
confidence: 99%
“…The genomic sequence of S. eubayanus was highly homologous to the non-S. cerevisiae portions of the S. pastorianus genome, suggesting that the hybridization event that gave rise to S. pastorianus occurred between S. cerevisiae and S. eubayanus, presumably following the incidental importation of S. eubayanus into Europe, although the exact source of the S. eubayanus parent remains controversial (Libkind et al 2011;Bing et al 2014).…”
Section: S Pastorianusmentioning
confidence: 99%